PRE-SERVICE MATHEMATICS TEACHERS’ CONCEPTION OF HIGHER-ORDER THINKING LEVEL IN BLOOM'S TAXONOMY - Damianus D Samo (IKIP Siliwangi and I-MES, 2017)
The purpose of this study is to explore pre-service mathematics teachers' conception of higher-order thinking in Bloom's Taxonomy, to explore pre-service mathematics teachers' ability in categorizing six cognitive levels of Bloom's Taxonomy as lower-order thinking and higher-order thinking, and pre-service mathematics teachers' ability in identifying some questionable items as lower-order and higher-order thinking. The higher-order thinking is the type of non-algorithm thinking which include analytical, evaluative and creative thinking that involves metacognition. This research is a descriptive quantitative research. The data were analyzed and visualized by percentages and diagrams. The participants are 50 Third-Year Students of Mathematics Education Department at Universitas Nusa Cendana. The results showed: (1) pre-service mathematics teachers' conception of lower-order and higher-order thinking more emphasis on the different between the easy and difficult problem, calculation problem and verification problem, conceptual and contextual, and elementary and high-level problem; (2) pre-service mathematics teachers categorized six cognitive levels at the lower-order and higher-order thinking level correctly except at the applying level, preservice mathematics teachers placed it at the higher-order thinking level; (3) pre-service mathematics teacher tend to made the wrong identification of the test questions that were included in the lower-order and higher-order thinking. One of the recommendations is pre-service mathematics teachers should be familiarized of higher-order thinking questions start from their first-year of study in University.Â